THE POWER OF MONEY POLITIC IN THE NOVEL NAMAKU SUBARDJO BY HAPSARI ANGGARINI: PERSPECTIVE HEGEMONY GRAMSCI (KEKUASAAN MONEY POLITIC DALAM NOVEL NAMAKU SUBARDJO KARYA HAPSARI HANGGARINI: PERSPEKTIF HEGEMONI GRAMSCI) - Dea Harumi Urbaningrum; Candra Rahma Wijaya Putra (Jurnal Gramatika, 2020)
This study aims to describe the power of money politics conducted by elite and middle social classes in the form of hegemony. The hegemony that occurs in the novel Namaku Subardjo y Hapsari Hanggarini is a total or integral hegemony without coercion. Hegemony occurs because the main character never realizes that he is a hegemony by his employees. Uniquely, Jojo's employees were hegemony by his party's acquaintances. The object of research or data source is the novel Namaku Subardjo by Hapsari Hanggarini. Data is obtained from sentences or dialogues, units of stories that lead to social class and money politics. The research procedures carried out are: 1) reading the novel as a whole, 2) collecting and making data sources, 3) inventing data based on theory, 4) analyzing data and interpreting data. Discussion of the data in the form of description. The instrument used was researchers who were assisted with books and other supporting media. The discussion in the novel is that there are social classes that influence hegemony, namely high and middle social classes. Money politics happens in the novel without violence and volunteers to do it. The strong hegemony that is done, makes the main character does not stop to do money politics.